What lessons can Asia draw from capital controls in Brazil during 2008 - 2012? - Yothin Jinjarak; Ilan Noy; Huanhuan Zheng (Asian Development Bank Institute (ADBI), 2013)
Driven by waves of foreign capital inflows and outflows, Indonesia, the Republic of Korea, and Thailand - among several other emerging markets - have resorted to capital control policy since 2006. Are capital controls effective? Controls on capital inflows have been experiencing a renaissance since 2008, with several prominent Asian and Latin American countries implementing them. We focus on Brazil, which instituted five changes in its capital account regime over 2008 - 2011. Using the synthetic control method, we construct counterfactuals (i.e., Brazil with no policy change) for each of these changes. We find no evidence that any tightening of controls was effective in reducing the magnitudes of capital inflows, but we observe some modest and short-lived success in preventing further declines in inflows when the capital controls were relaxed. We hypothesize that price-based capital controls' only perceptible effect is to be found in the content of the signal they broadcast regarding the government's larger intentions and sensibilities. In the case of Brazil, its left-of-center government's willingness to remove controls was perceived as a noteworthy indication that the government was not as hostile to the international financial markets as many expected it to be. Based on these findings, the effectiveness of capital controls should be viewed on a case-by-case basis, together with the political economy considerations, and other policy tools, i.e., foreign exchange intervention.
Keywords: F32; G23; E60; 330; capital control; brazil; global financial crisis; mutual fund flows; exchange rate; Kapitalimport; Kapitalverkehrskontrolle; Brasilien; Vergleich; Asien